2018
DOI: 10.3174/ajnr.a5794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Genotype and Survival in Glioma Using Standard Clinical MR Imaging Apparent Diffusion Coefficient Images: A Pilot Study from The Cancer Genome Atlas

Abstract: wild-type glioma showed lower ADC values, which also correlated with poor survival in both -mutant and wild-type gliomas, irrespective of histologic grade. A subgroup with -mutant gliomas with lower ADC had dismal survival similar to that of those with wild-type gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 39 publications
8
39
1
Order By: Relevance
“…We hypothesize that with many patients undergoing CT at diagnosis, consistent availability of this and/or SWI imaging could further increase observer certainty and concordance. In keeping with our observations (model B), absence of cysts has been proposed previously as an IDH wt glioma feature (33).…”
Section: Test Samplesupporting
confidence: 92%
“…We hypothesize that with many patients undergoing CT at diagnosis, consistent availability of this and/or SWI imaging could further increase observer certainty and concordance. In keeping with our observations (model B), absence of cysts has been proposed previously as an IDH wt glioma feature (33).…”
Section: Test Samplesupporting
confidence: 92%
“…ADC values obtained from standard clinical DWI with a simple, two-dimensional region-of-interest (ROI) quantification were lower in IDH wild-type than in IDH-mutant LGG, thus supporting the importance of the extraction of quantitative, radiomic metrics for meaningful dMRI analysis [ 36 ]. More recently, a pilot study from The Cancer Genome Atlas has demonstrated that ADC values obtained from clinical DWI correlated with survival in patients with IDH-mutant and IDH wild-type gliomas regardless of WHO grade, suggesting a potential usefulness of quantitative ADC estimates as a prognostic marker to enhance risk stratification in brain gliomas [ 37 ].…”
Section: Imagingmentioning
confidence: 99%
“…Our study is not dependent on advanced sequences, we used only the basic sequences with diffusion weighted imaging (DWI) sequence to classify the gliomas. A pilot study by Wu et al have tried using DWI imaging to predict survival, but it is dependent on IDH mutation (22) . Thus, none of the study have looked holistically at gliomas to come up with a radiological classification system independent of the histological and genetic information.…”
Section: Discussionmentioning
confidence: 99%